A strategy of scaffolding development to ıncrease students’ problem-solving abilities: The case of physics learning with causalitic-thinking approach - Rokhmat, Joni; Marzukı; Wahyudı; Putrie, Syandy Dwirahayu (Journal of Turkish Science Education, 2019)
Unlike general approaches to learning, the Causalitic-Thinking Approach, aims to construct phenomena that have more than one possible answer. However this approach requires scaffolding strategies. This study aims to investigate the strategy of developing scaffolding in learning with the Causalitic-Thinking Approach to increase students’ problem-solving abilities; namely, understanding, selecting, differentiating, determining, applying, and identifying. An embedded experimental two-phase design with a sample of 33 senior high school students (21 -females, 12 -males). The differences between pre- and post-tests, and between the problem-solving ability -gain of the low and high groups were tested with Wilcoxon signed-ranks-test. Results show that the scaffolding that was implemented was effective in increasing problem-solving abilities but there was no significant difference between the two groups of students.